Assessment of Trace Element Daily Intake Based on Consumption Rate of Foodstuffs in Bandung City - E. Damastuti; W.Y.N. Syahfitri; M. Santoso; D.D. Lestiani (Atom Indonesia, 2012)
Trace elements are required by human body and have a variety role in biochemical functions mostly as catalyst for enzymatic activity in human body. Some trace elements are essential since they are inadequately or not synthesized by human body. The deficiency or excess of those essential trace element may cause disease and be deleterious to health. Since food is the primary source of essential elements for humans and it is an important source of exposure to toxic elements either, the levels of trace elements in consumed food products must be determined. The determination of trace elements content in foodstuffs widely consumed in Bandung city were conducted to assess their daily intake and contribution to the recommended dietary allowance (RDA) values. Food samples were collected from traditional markets spread across five regions of the Bandung city and analyzed using neutron activation analysis (NAA). Quality control of data analysis was assessed using SRM NIST 1567a Wheat Flour and 1568a Rice Flour and gave good results with % recovery, 93.2 – 104.8%; and %CV, 3.8-11.6%. A large variability of essential trace elements concentration in all types of foods analyzed were observed. The daily intake of Cr, Co, Mn, Se and Zn were supplied enough by the diet, except for Fe which found that almost all the foods analyzed were not give a satisfying contribution to the RDA value of Fe. These result were expected could provide information of nutritional status of the society and can be a reference for government and related institution to effectively making policies and solution for public health improvement.Received: 5 December 2011; Revised: 7 April 2012; Accepted: 16 April 2012